Factors Affecting Adoption Of E-Business And Organizational Performance: A Proposed Framework - Mohamed Saleh Abd AL Khuja; Zainalabidin Bin Mohamed (International Institute of Engineers, 2024)
The main purpose of this study is to identify factors affecting E-business adoption and organizational performance. Due to rapid globalization and competition, there is a necessity of change in skills and practices in dealing with customers and suppliers to complete business transaction enhancing productivity, knowledge management and organizational performance. In Libya many enterprises considers technology adoption as an extra cost facing a new challenge of adopting technologies. Firms in Libya are facing competitive pressure that creates urgency of working efficiently in the competitive market. This makes an urgent need of e-business adoption strengthening their capacity and capability. This paper therefore develops a framework for e-business adoption which is composed of five innovation factors. The proposed framework is then used to guide future study in exploring its adoption and organizational performance. The proposed framework will be empirically validated by self-administered survey questionnaire among small and medium enterprises of Libya. Keywords—Diffusion of Innovation Theory, E-business adoption, organizational performance, Libya.